2008
DOI: 10.1007/s10333-007-0100-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of water balance in a rainfed paddy field in Northeast Thailand

Abstract: Rice productivity in rainfed paddy fields varies with seasonal changes of water availability in which the conditions of flooding are affected by the water balance. Hydrometeorological measurements were performed in a rainfed paddy field in Northeast Thailand from July 2004 to December 2006 to analyze the water balance. As a result of our measurements, climatologically conditions were classified as semi-humid with an annual precipitation of 1,100 mm/year and annual potential evaporation of 1,660 mm/year in both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…This is in agreement with many previous field surveys, which reported that transplanting dates varied widely even within a small watershed (Miyagawa et al 1999;Homma et al 2001). Even where only limited rainfall is available, a certain portion of the paddy field can collect ponding water because of its lower elevation or lower permeability of the soil to water (Tsubo et al 2007;Goto et al 2008). In these situations, paddy fields will be established earlier where ponding water can be obtained easily and later where water availability is lower.…”
Section: Relationship Between Transplanting Date and Precipitationmentioning
confidence: 98%
“…This is in agreement with many previous field surveys, which reported that transplanting dates varied widely even within a small watershed (Miyagawa et al 1999;Homma et al 2001). Even where only limited rainfall is available, a certain portion of the paddy field can collect ponding water because of its lower elevation or lower permeability of the soil to water (Tsubo et al 2007;Goto et al 2008). In these situations, paddy fields will be established earlier where ponding water can be obtained easily and later where water availability is lower.…”
Section: Relationship Between Transplanting Date and Precipitationmentioning
confidence: 98%
“…It is clear from the studies listed that a focus on water use as quantified by different measures of evapotranspiration (actual, as in Bastiaanssen and Zwart, ; potential, as in Goto et al., ; and reference, as in Allen et al., ) dominates the existing knowledge. However, only a small part of this literature considers the lower Mekong basin, and an even smaller part considers Cambodia.…”
Section: Water Productivity: a Brief Review Of The Ex Ante Literaturementioning
confidence: 99%
“…Northeastern Thailand has a semi-humid tropical climate which is characterized by rainy (May-October) and dry (November-April) season (Goto et al 2008). Cassava is a cash crop of smallholder farmers in northeastern Thailand.…”
Section: Introductionmentioning
confidence: 99%